NEEDS ANALYSIS IN HUMAN RESOURCE INFORMATION TECHNOLOGY - Joko Susilo; Rafael Abdul Gafar, Ir. Rafael Abdul Gafar, Ir. (Jurnal Sistem Informasi, 1995)
By looking at the growing market for information technology software, hardware andprofessional Jada from the year 1992 - 1995 is increasing from a total of 520 millionU.S. dollars - 752 million U.S. dollars, and to see the development of marketcomposition per sector of industry generally, Distribution, Production, and of thefinancial year 1992 - 1995, also increased the 520 million-720 million U.S. dollars toU.S. dollars then it can certainly be a lot of human beings needed to master the fieldof information technology in line with the needs of professionals in information onvarious industrial sectors in accordance with market labor.Improvement of the need for human resources could also look at the projections ofthe need for human resources in the field of information technology from 1992 - 2020the next. from these projections could see how the book of human resource needs inthe field of information technology is always increasing.